Menekan Kemiskinan Petani Pedesaan: Reorganisasi Petani Berdikari - Damayanti, Irma (Lembaga Kajian, Penelitian dan Pengembangan Mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
Agriculture is one of the strategic sectors to growth up the national economic. The real contribution applied in supplying food commodity, employment absorption, and also as foreign exchange sources. Rural as an epicentrum of agriculture activity should also can increase the prosperity in every citizen, but in empirical reality show the opposite condition. Up till now, Agriculture just focus on how to increasing productivity to fulfill the Market’s needs without any increasing in farmer’s prosperity. Increasing of productivity without any effort in increasing of farmer’s prosperity being a problem that make in raising imbalance in their prosperity. So that, it’s need initiative form the farmer to make them do not depend on government policy. Reconstruction of organizational essential need to be developed to make “Petani Berdikari”. The strength of farmer’s organization will increase the farmer’s prosperity because the farmer’s organization backed up all of the farmer’s activity. Pertanian merupakan sector strategis untuk menumbuhkan perekonomian nasional. Kontribusi nyata teraplikasikan pada penyediaan bahan pangan, penyerapan tenaga kerja, dan juga sebagai sumber devisa Negara. Pedesaan sebagai episentrum kegiatan pertanian seharusnya bisa meningkatkan kesejahteraan setiap penduduknya, namun realita empiric menunjukkan hal yang sebaliknya. Pertanian selama ini terfokus pada bagaimana produktivitas dan pemenuhan kebutuhan pangan tanpa dibarengi dengan perhatian akan kesejahteraan petani. Tulisan ini mencoba merefleksikan bagaimana keadaan petani pedesaan. Peningkatan produktivitas yang tidak dibarengi dengan peningkatan pendapatan masyarakatnya menjadi permasalahan yang berujung pada ketimpangan kesejahteraan manusianya. Oleh karenanya diperlukan inisiatif aktif petani agar tidak berpangku tangan pada kebijakan pemerintah. Rekonstruksi esensi organisasi petani perlu diupayakan agar terwujudnya petani berdikari (berdiri di atas kaki sendiri). Kuatnya organisasi petani akan meningkatkan kesejahteraan petani karena organisasi petani menanungi segala aktivitas pertanian petani.